Musical ecologies : instrumental music ensembles around the world - De Bruin, Leon R.; Southcott, Jane (Routledge, 2022)
"Community music around the world reflects the growing and diverse ways humans collectivize and express themselves in ways that articulate our cultural, social and environmental complexity. Revisiting, redevising and reimagining some of the field's approaches, ideologies and contexts, this co edited volume investigates beyond generalist intercultural and internationalist concepts to reveal the complexity of social ways people come together to make music, and to making music be central to this sociality. The authors explore the role community music plays out around the world and how various instrumentally based music making communities operate as ecologies that allow notions of social, political and cultural agency and identities. Chapters cover various instrumental community music ensembles, observing how they, as social microcosms of change and stasis, provide working methods new and old, extol values and model ethical behaviors that are fluid and dynamic, steadfast and unyielding and that contribute to the ebb and flow of people and their agency that remains under researched. Insights are provided on variously functioning ensembles through the world, showing how myriad instrumental music communities act as drivers, complex environments and apparati for musical and social expression that accommodates the musical aspirations of their members. Taken as a whole, this book explores community music and what music making means to people in the twenty first century"--